A surface chemical analysis strategy for the microstructural changes in a CuAgZrCr alloy cast under oxidation conditions - Maffia, Ernesto Gustavo (2024)
The aim of this work was to determine the behavior of alloy elements and compounds formed during solidification in the manufacturing process of the CuAgZrCr alloy under an oxidizing environment. Bulk and surface analysis techniques, such as Scanning Electron Microscopy (SEM), X-ray Photoelectron Spectroscopy (XPS), Raman and X-ray diffraction (XRD) were used to characterize the phases obtained in the solidification process. In order to focus the analysis on the on grain boundary interface, partial removal of the matrix phase by acid attack was performed. The compositional differences obtained by SEM-EDX, Raman and XPS on post-manufacturing materials allowed us to conclude that the composition of grain boundaries of the alloy is directly influenced by the oxidizing environment of alloy manufacturing.